Isolation and Purification of the Schizont Stage of Theileria annulata from Host Leukocytes through Novel Biochemical Techniques - Haghparast, Dr. Alireza (Asian Journal of Pharmaceutics (AJP), 2018)
Background: The protozoan intracellular parasite, Theileria annulata, induces uncontrolled proliferation and transformation in bovine B lymphocytes and monocytes in the blood circulation and lymph nodes of host cells in macroschizont stage of life cycle. The development of a rapid and efficient technique is likely to necessitate for isolation purified schizonts from host cells for incorporation in isolation highly purified RNA, protein, or glycoproteins of schizonts from host cells. Materials and Methods: This study approved based on the aerolysin - nocodazole. Aerolysin that purified from gram-negative pathogen aeromonas hydrophila has an ability to form discrete channels and unstable a eukaryotic cell membrane in 0Â°C and low concentration. Nocodazole used for parasite separation from Microtubule network of infected lymphocytes and monocytes. Results: In purified schizonts, no large nucleus of host cell visualize in Giemsa and 4â€™,6-diamidino-2-phenylindole staining. Schizonts are free and intact from host cells. Conclusions: intact T. annulata schizonts suitable for RNAs, proteins, glycolipids, and glycoproteins of schizonts free of host debris.